Use of the Optically Stimulated Luminescence Dating and X-Ray Fluorescence Spectrometry Methods as Tools in Paleoseismology - Tsodoulos, L. M.; Stamoulis, K.; Papachristodoulou, C. A.; Ioannides, K. G.; Pavlides, S. (HNPS Advances in Nuclear Physics, 2019)
We have investigated the application of luminescence dating to sediment and pottery samples from a paleoseismological trench excavated in the Gyrtoni Fault, Tyrnavos Basin, Central Greece. The samples were dated following the optically stimulated luminescence (OSL) dating method, using the Riso TL/OSL DA-20 reader. The OSL ages were obtained from chemically purified quartz and a single-aliquot regenerative-dose (SAR) protocol was followed for the equivalent dose (De) determination. Additionally, samples were collected and analyzed with the method of X-ray Fluorescence (XRF) spectrometry, in order to assess their elemental composition. Radioisotope sources (109Cd and 241Am) were used for sample excitation, while X-ray spectra were acquired using a Si(Li) detector coupled with standard electronics. The XRF data were submitted to principal component analysis (PCA). This statistical handling aimed to distinguish from which part of the upthrown fault block scarp-derived colluvium and alluvial deposits, parts of the downthrown block were derived and thus estimate the displacement. The results indicated that both the OSL dating method and the XRF analysis combined with PCA can serve as useful tools for paleoseismological investigations.